IMPACT OF CARBON TAXES ON COMPANY FINANCE - Euriver Zega; Merwati Waruwu; Ningsih; Muammar Khaddafi (International Conference on Health Science, Green Economics, Educational Review and Technology, 2023)
Carbon tax is new matter for company in Indonesia nowadays. The tax that charges for carbon is embodiment of constitution commitment. Indonesia government make a promise that written in Indonesia Constitution, which is the promise is to provide all of Indonesian People and give everyone healthy living environment. This promise has evolved into a carbon tax which is expected to curb corporate carbon spreading. This study will be based on Indonesia law Number 7 of 2021 on the Harmonization of Tax Regulation and Presidential Regulation Number 98 of 2021 on the Implementation of Carbon Value.